Sulfonamidlerin amino kolonlarına HPLC analizi - Özer, Lale Meyancı (My University, 2005)
Bu çalışmanın amacı; Sulfonamidlerin,HPLC analizinde her zaman kullanılan C-18 Kolon'dan farklı olarak,Sülfamid grubu içeren yeni bir kolon dolgu maddesiyle analizinin yapılmasıdır.Bu amaca yönelik olarak serbest amino ve sülfamid grubu içeren modifiye silikageller sentezlenmiş ve ele geçen dolgu maddeleri Sülfonamidlerin analizinde denenmiştir. Sonuçlar irdelendiğinde amino türevli kolon dolgu maddesinin Sülfonamidlerin ayrılmasında başarılı olduğu buna karşı Sülfamid grubu içeren kolon dolgu maddesinin ise yetersiz olduğu görülmüştür Bundan başka İlsan İltaş İlaç Fabrikasından alınan Bacton Tabletlerin karışımında bulunan Sülfametoksazol'ün kantitatif tayini, her zaman uygulanan C-18 Kolondan farklı olarak Hypersil H3APS kolonla denenmiştir. Bu kolonun (Hypersil H3APS), çeşitli kromatografik koşulları deneyerek, çok sayıda sülfonamid bileşeni içeren örneklerin tayininde geniş bir kullanım alanına sahip olacağı düşünülmektedir. Şubat 2005 Lale Meyancı Özer .

In this study, for the HPLC analysis of sulfonamides, along with previously used C-18 packed column, new types of packed columns containing amino(commercial) and sulfamide derivatives of silicagel were employed. With the aim of obtaining of packing material including sulfamide group, the silica gel derivative with free amino group was synthesized first. Later, by the reaction of amino group in the silica gel structure with p-toluenesulfonylchloride in a given condition, modified silica gel was obtained comprising sulfamide group. The packing materials obtained with mentioned route were tested in the chromatographic(HPLC) analysis of sulfonamids by packing the column. When the results were examined, it has been seen that the packing material with amino-derivative was successful in seperating the sulfonamides. However, it has been determined the performance of packing material including sulfamide group was insufficient about seperating sulfonamides. In addition, the quantitative analysis of sulfamethoxazole in Bacton Tablets supplied from İlsan-İltaş Medicine Factory has been essayed with a Hypersil (H3APS)-amine column instead of C-18 column employed in routine analyses. It has been estimated that this column (Hypersil-H3APS) will gain wide application area in the determination of samples containing numerous sulfonamides compounds by trying different chromatographic conditions. February 2005 Lale Meyancı Özer
Keywords: Analitik Kimya